Comparison study: Inflationary effect of crude oil price in the case of Malaysia and Turkey / Ahmad Rabani Abdul Halim - Abdul Halim, Ahmad Rabani (2007)
The effect of crude oil prices on inflation rate has been continues to be an important topic. Inflation, in the areas of macroeconomics, is always related to high prices of good and services, unemployment, wages and other economic variables. From the view of financial economies, inflation is the risk to the business, investors, and borrower of the fund. This is because; there is a relationship between inflation and interest rate. This study provides the investigation of the relationship between world crude oil prices and inflation rate in Malaysia and Turkey using Pearson's product moment correlation and Single Regression model. The purpose of the study is to determine the correlation and the relationship between oil prices and inflation rate. Furthermore, it wants to identify the strength of the association between these two variables. In order to obtain better analysis, the data of world crude oil prices and inflation rate in Malaysia and Turkey were analyzed in time series of 16 years from 1990 until 2005. the result shows that oil prices and inflation rate in Malaysia have a negative relationship while there are a significance positive relationship between oil prices and inflation in Turkey.